2009
DOI: 10.1002/ca.20756
|View full text |Cite
|
Sign up to set email alerts
|

Translation and rotation movements of the mandible during mouth opening and closing

Abstract: To assess the relative contribution of rotation and translation of the temporomandibular condyle-disc assembly during opening and closing movements, free movements of maximum mouth opening and closing were recorded in healthy subjects (12 men, 14 women) using an optoelectronic three-dimensional motion analyzer. For each subject, the displacement of the lower interincisal point, the path of the condylar reference point, the degree of rotation around the three orthogonal rotational axes, and the relative contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
1
39
0
3
Order By: Relevance
“…Lewis et al (8) found no relationship between maximum opening and mandible size, while Gallagher et al (29) found no relationship with body height. However, Mapelli et al (30) found higher mandibular opening values in males than in females, a difference that disappeared when mandibular radius was applied as a correction factor. More specific studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Lewis et al (8) found no relationship between maximum opening and mandible size, while Gallagher et al (29) found no relationship with body height. However, Mapelli et al (30) found higher mandibular opening values in males than in females, a difference that disappeared when mandibular radius was applied as a correction factor. More specific studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the condyle cannot move back to the glenoid fossa because no translational movement of the condyle is possible in this rotation process (Fig 1D) in contrast to the existence of actual condylar movement. 4 Thus, the rotated mandible was anterior to the mandible in the intercuspal position (Fig 1D), and the actual mandibular-cranial and mandibular-maxillary relationship in the anteroposterior and transverse direction cannot be achieved by this rotation. Therefore, other methods were necessary to move the mandible to the intercuspal position to obtain an actual mandibular-cranial and mandibularmaxillary relationship.…”
Section: Casementioning
confidence: 95%
“…The range of mandibular movements was assessed at maximum mandible descent (MMO), protrusion (MMP) and laterotrusions (MML), calculating the projections of the displacement of its landmarks (cranial–caudal, ventral–dorsal, medial–lateral) as well as its sagittal, coronal and horizontal angles (Fig. S1, Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…During mouth opening and closing, the peak‐to‐peak lateral deviation of IP was computed; also, the mean velocity of both IP and CRPs in the two phases was calculated in the temporal span between 5% and 90% of MMO. The sagittal mandibular movement during mouth opening and closing was further divided into its rotation and translation components ; in each frame of motion, the relative percentage contribution of the two components to the total movement was calculated for each condyle. To compare different subjects, the mandibular movement was normalised on MMO distance (sagittal projection): mouth opening and closing were sampled in 10% steps, and for each step, the corresponding percentage of translation component (CRP translation index) was calculated for both condyles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation